The best exercises from top 20 by health-related indicators - Skurvydas, Albertas; Istomina, Natalja; Valanciene, Dovilė; Dadeliene, Ruta; Jamontaite, Ieva Egle; Lisinskiene, Ausra; Sarkauskiene, Asta; Majauskiene, Daiva (Frontiers in Public Health, 2025)
BackgroundThe study aimed to determine whether participation in professional sports, exercise in a sports/health center, or independent exercise (dependent variables) is associated with 11 health behavior-related indicators (independent variables) compared to having no exercise.MethodsThe survey involved 293 professional Lithuanian athletes, 2,120 who exercise independently or in a sports/health centre and perform at least one of the 20 most popular exercise types in Lithuania (hereafter referred to as “E-20”), and 3,400 who do not exercise. The participants were aged 18–74 years.ResultsThe study uniquely examines a comprehensive range of 11 health-related indicators: body mass index, subjective health, depressed mood, stress, sedentary behavior, physical activity, sleep, alcohol consumption, smoking, overeating, and breakfast consumption. We examined whether these indicators differ between the three populations studied, whether they are associated with specific types of the E-20 exercises, and whether these patterns differ between men and women.ConclusionOur study indicates that participants who engaged in physical activity generally scored higher on various health-related scales compared to those who were inactive. These benefits include reductions in depressed mood, stress, body mass index, and binge eating, as well as improvements in the regularity of breakfast consumption, vigorous physical activity, moderate to vigorous physical activity, and sleep duration (notably in men).